Value of global longitudinal strain in assessing radiation-induced heart disease in breast cancer: systematic review and meta-analysis - XU Xiaofei, ZHANG Lixia, DAI Heyang, CHEN Lingyun, XUE Jiaojiao, LI Qingxia (Zhongguo aizheng zazhi, 2022)
Background and purpose: Breast cancer has overtaken lung cancer as the most common malignant tumor in women. Early breast cancer patient can achieve a long survival time after comprehensive treatment, however the cardiotoxicity caused by radiotherapy may affect its long-term prognosis. Therefore, early monitoring of radiation-induced heart disease is important for improving the survival of breast cancer patients. Speckle-tracking echocardiography (STE) is a new technique to study myocardial deformation. Global longitudinal strain (GLS) is a good parameter for evaluating early cardiotoxicity caused by radiotherapy. The purpose of this study was to evaluate the value of GLS in evaluating radiotherapy-induced early cardiotoxicity in breast cancer. Methods: PubMed, EMBASE, Web of Science, Cochrane Library, Wanfang and China National Knowledge Infrastructure (CNKI) databases were searched by computer from January 2010 to March 2022. According to the pre-set inclusion and exclusion criteria, screening studies was performed using GLS and left ventricular ejection fraction (LVEF) to evaluate myocardial function changes during and after radiotherapy for breast cancer. Two researchers independently conducted literature screening and data extraction. Review Manager5.4 analysis software was used for data analysis. Results: Finally, 9 studies were included, involving a total of 543 patients. Meta-analysis results showed that LVEF of patients with left breast cancer decreased slightly immediately after radiotherapy, and WMD was -0.98. LVEF of those patients increased at 6 months after radiotherapy, and the WMD was -0.83, which was still lower than baseline. LVEF was almost unchangeable after radiotherapy for right breast cancer. GLS of left-sided breast cancer patients decreased significantly immediately after radiotherapy, at 6 weeks, 6 months and 12 months after radiotherapy, and WMD was 1.57, 1.84, 1.04 and 1.69, respectively. The differences were statistically significant. There was no significant heterogeneity among the studies. However, there was no significant change in GLS after radiotherapy for right breast cancer. There was no significant difference in GLSr between breast cancers of different sides. Conclusion: GLS may be a good predictor of radiation-induced heart disease in patients with left-sided breast cancer.